Comparison of Criminal and Civil Liability of Corporations in Environmental Pollution - Gunawan, Hendra; Hosein, Zainal Arifin (Yayasan Meira Visi Persada, 2024)
This research discusses the comparison between criminal and civil liability imposed on corporations in cases of environmental pollution, as well as analyzing the effectiveness and impact of the application of both types of sanctions. In environmental pollution cases, corporations can face criminal sanctions in the form of fines and administrative actions aimed at providing deterrent effects, while civil sanctions focus more on compensation that must be paid to affected communities. The research employs a normative legal method with a legislative and conceptual approach, allowing for an in-depth examination of legal provisions governing criminal and civil liability for corporations that cause environmental pollution. The analysis indicates that the application of criminal and civil sanctions plays different roles in environmental law enforcement; criminal sanctions emphasize preventive and repressive effects against corporate violations, while civil sanctions serve as a mechanism for restoring the rights of affected communities. It is hoped that the findings of this study can contribute to the improvement of environmental legal regulations, particularly regarding the regulation of sanctions against corporations to create a more sustainable environment.